2019
DOI: 10.1177/1477760619895025
|View full text |Cite
|
Sign up to set email alerts
|

Water-swellable rubber blend from epoxidized natural rubber and superabsorbent polymer composite

Abstract: Epoxidized natural rubber (ENR) and a superabsorbent polymer composite (SAPC) along with other minor components were mechanically blended in an internal mixer (Brabender Plasticorder) at 40°C and 60 r/min rotor speed with 80% fill factor. The SAPC was synthesized by grafting polyacrylamide onto hydroxyethyl cellulose backbones and adding bentonite clay. The first water-swelling behavior was investigated with alternative epoxidation levels of the ENR. Water-swellable rubber (WSR) performed well in terms of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…This reducing trend in strength upon swelling may be due to breaking of total network density (both physical and chemical networks) as water leached into bulk matrices, similar to those earlier observed by Adair et al [ 51 ] The order of the effect of water swelling on the decreasing tensile strength of the samples (SR1‐SR3) is; SR1 > SR3 > SR2, this followed the decreasing order of network density ( N ); SR1 > SR3 > SR2. With reference to Table 3, SR1 is about 2402 and 1282.4% higher in crosslinking density than SR2 and SR3 respectively, hence SR1 is higher even in extreme swelling state.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This reducing trend in strength upon swelling may be due to breaking of total network density (both physical and chemical networks) as water leached into bulk matrices, similar to those earlier observed by Adair et al [ 51 ] The order of the effect of water swelling on the decreasing tensile strength of the samples (SR1‐SR3) is; SR1 > SR3 > SR2, this followed the decreasing order of network density ( N ); SR1 > SR3 > SR2. With reference to Table 3, SR1 is about 2402 and 1282.4% higher in crosslinking density than SR2 and SR3 respectively, hence SR1 is higher even in extreme swelling state.…”
Section: Resultssupporting
confidence: 81%
“…However, as clearly seen, the swellability of the current composition was retained at levels which still qualified them as suitable WSE. Comparatively, the effect of PEO in the current composition (C) degree of swelling (%) versus time and (D) absorption rate of samples yielded higher water swelling performance than those reported by Adair et al [51] whose composition (ENR-SAP) swollen in water for 30 days recorded a swelling degree of $35%.…”
Section: Water-swelling Degree Analysismentioning
confidence: 63%
See 1 more Smart Citation
“…Similar behavior was also observed in the preparation of WSR from ENR and superabsorbent polymer composite. 38 When comparing ENR 25 and ENR 50, it was observed that the tensile strength of WSR from ENR 50 was higher than that of WSR from ENR 25. However, there was no significant difference in elongation at break and hardness between the two.…”
Section: Mechanical Properties Water Swelling and Volume Changementioning
confidence: 98%
“…Owing to excellent water absorbency, retention, and hydrogel properties, SAPs have obtained extensive applications ( Wu et al, 2000 ; Zohuriaan-Mehr and Kabiri, 2008 ; Zohuriaan-Mehr et al, 2010 ; Ahmed, 2015 ), especially in fields such as hygienic products ( Shahi et al, 2017a ; Shahi et al, 2017b ), agriculture ( Zhang et al, 2014a ; Zhang et al, 2014b ; Guilherme et al, 2015 ; Fang et al, 2018 ), pharmacy and medicine ( Mastropietro et al, 2012 ), tissue engineering ( Stamatialis et al, 2008 ), wound dressings ( Wiegand et al, 2011 ; Capanema et al, 2018 ), soil-less cultivation ( Takeuchi, 2019 ), biosensors ( Qasemi and Ghaemy, 2020 ), smart materials ( Vosseler et al, 2012 ), electrical applications ( Boruah et al, 2015 ), construction ( Vieira et al, 2014 ), fibers and textiles ( Majchrzycka et al, 2017 ), separation/water treatment ( Zhou et al, 2016 ), sludge/coal dewatering ( Zhang et al, 2017 ), and water-absorbing rubber ( Adair et al, 2020 ). So far, the hygienic applications, particularly disposable diapers as described by Wu et al, 2000 , have occupied the largest market share of SAP products and the agricultural applications the second largest.…”
Section: Introductionmentioning
confidence: 99%